Carbon footprint assessment and crashworthiness evaluation of alloy steel W-beam guardrails - Shuai Gong; Wendong Fan; Haoze Zhao; Zhihao Zhang; Shuming Yan (PLoS ONE, 2026)
In response to the dual demands of enhancing safety and greening transportation infrastructure under China’s “Dual Carbon” goals, this study overcomes the limitations of traditional guardrail materials and processes by proposing and validating a synergistic pathway for optimizing both the safety and carbon emission reduction of alloy steel corrugated beam guardrails. A systematic “material design – process optimization – performance verification – environmental assessment” framework was established. High-performance 700L-grade alloy steel was produced through low-carbon alloy design combined with ESP short-process rolling technology. Its safety performance was quantitatively evaluated via SB-level full-scale vehicle crash tests, and its life-cycle carbon footprint was quantified using an ISO 14067-compliant model implemented in eFootprint software with the CLCD database. The results demonstrate that the alloy steel achieves a synergistic optimization of strength and plasticity, with a tensile strength of 766–781 MPa and a product of strength and elongation (PSE) exceeding 0.175 GPa·%. In the full-scale vehicle crash tests, all occupant risk indicators were superior to the safety limits. For instance, the key risk parameters for the small passenger car, such as the longitudinal velocity (V x = 4.3 m/s) and the lateral acceleration (a y = 126.0 m/s²), demonstrated excellent performance. The maximum dynamic outward inclination equivalent values for the medium and large trucks were 1.75 m and 2.45 m, respectively. These results confirm that the safety performance of the guardrail fully meets the SB-level standard, even with a lightweight design featuring a 25% reduction in beam thickness and a 50% reduction in post thickness. Life-cycle analysis revealed that the carbon footprint per kilometer of guardrail was reduced to 80.86 t CO 2 e, representing a 73.8% reduction compared to the conventional solution. Sensitivity analysis identified iron input and electricity consumption as the core influencing parameters. Furthermore, a cost-benefit analysis indicated superior life-cycle cost advantages. This study elucidates the mechanism for achieving synergistic gains in safety and emission reduction through material and process innovation, providing a systematic solution and data support for the green, low-carbon, and safe transformation of highway infrastructure.